Hubungan Pemberian ASI Eksklusif dan Imunisasi dengan Pertumbuhan Bayi Usia 0-6 Bulan - Ekdeni Aifa, Wira; Heryudarini, Heryudarini; Mitra (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2015)
Weight gain in infancy is very important to be controlled due to this phase is the golden period of growth and development of their life. Babies need good parenting from their mother, that are exclusively breastfeeding and immunization that aims to have normal growth. The study aim was to determine the association of parenting that was exclusively breastfeeding and immunization with infant growth of aged 0-6 months in Puskesmas Garuda Pekanbaru. Study design was cross-sectional. Sample was 210 infants, sampling method with systematic random sampling. The data analysis was multiple logistic regression. Results of this study shown the proportion of un-normally growth was 1% and factors that associated with infants growth was exclusive breastfeeding (POR 2,7; 95% CI : 1,042 - 6,984), immunization (POR 7,5; 95%CI:3,114-18,183), mother’s education (POR 2.8; 95% CI:1.204-6.546), mother’s knowledge (POR 4,6; 95% CI:1,904-11,299), frequency of morbidity (POR 2,4; 95%CI:1,015-5,796). It was recommended for mothers with infants aged 0-6 months in order to provide good parenting to the baby by giving exclusive breastfeeding and complete immunization.